Mechanisms of aging in the cardiovascular system: challenges and opportunities - Zhao, Xiaoying; Yang, Xinyue; Lin, Yumeng; Lei, Ruolan; Ding, Wei; He, Xinying; Cao, Ying; Zhang, Dechou; Liu, Ping; Liang, Meirou; Han, Zhongyu; Jiang, Yu (Frontiers in Immunology, 2025)
Cardiovascular diseases (CVDs) pose a significant threat to the health of the elderly population. As the global population ages and medical management remains imperfect, reducing the medical burden of CVDs is of great importance. Aging is a complex process that contributes to the development and progression of CVDs through various mechanisms. The manuscript reviews the mechanisms of aging and their impact on the cardiovascular system. We explore the role of aging in the cardiac microenvironment, highlighting the changes that occur in the heart’s cellular and molecular landscape as a result of the aging process.